Sorption properties of activated carbons for the capture of methyl iodide in the context of nuclear industry. (April 2022) - Chebbi, M.; Monsanglant-Louvet, C.; Parent, P.; Gerente, C.; Coq, L. Le; Mokili, B.M.
Highlights: Activated carbons were tested for CH3 I capture under batch reactor configuration. Methyl iodide sorption kinetic curves have been described using the LDF model. Langmuir model parameters are compared at different temperatures and H2 O contents. CH3 I adsorption is sensitive to the micropores availability for low steam content. TEDA impregnation is crucial for strong CH3 I fixation at severe conditions. Abstract: In the present study, some commercially available activated carbons were evaluated towards the methyl iodide (CH3 I) capture in the context of nuclear industry. A specific methodology was implemented in order to establish structure-activity relationships between adsorbent characteristics and its adsorption behavior towards CH3 I. On the one hand, the investigated adsorbents were characterized by a combination of physico-chemical techniques. On the other hand, CH3 I retention performance from batch sorption tests under different conditions (temperature and relative humidity) was studied using an original experimental setup. In this work, two conditions were investigated: (i) T = 35°C, R.H. = 26 % ([H2 O] ∼15, 000 ppmv); (ii) T = 75°C, R.H. = 30 % ([H2 O] ∼130, 000 ppmv). Different trends were obtained depending on the investigated scenario. At ambient conditions (i), CH3 I adsorption performance was affected after KI/TEDA impregnation because of partial pore blockage phenomena induced by the of impregnants presence within the microporosity. However, TEDA impregnation was found to be required to enhance the trapping stability and to capture CH3 I with superior efficiency at higher temperature (ii). Graphical abstract: Image, graphical abstract .